PENGARUH PUPUK VERMIKOMPOS TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS JAGUNG (Zea mays. L) - Novi Nurlailah; Hidayat Bambang Setyawan (Universitas Trilogi, 2019)
Maize (Zea mays. L) is a source of carbohydrates as food, feed ingredients for livestock and industrial raw materials and bioethanol raw materials. To optimize the productivity of local maize, fertilization can be done. The use of organic fertilizers is very good for maintaining soil health, one of them is vermicompost. The application of vermicompost fertilizer is the right solution in this problem because composting of organic waste with the help of earthworms (Lumbricus sp.) contains high nutrients. The needs of adequate nutrient and growing environment will maximize the genetic potential of a variety. This research was conducted with the aim to determine the effect of vermicompost fertilizer on growth and yield of several maize varieties (Zea mays L). This study used a grooved plot design (Strip Plot) with 3 replications. The vertical path consists of 4 doses of fertilizer, namely P0 = 0 ton /ha, P1 = 4.5 tons/ha, P2 = 9 tons/ha, and P3 = 13.5 ton/ha. Horizontal path consists of 4 varieties, namely V1 = Dampit local variety, V2 = Arjuno superior variety, V3 = Karangploso local variety and V4 = Madura local variety (V4). Results of this study shows that fertilizer dose is 13.5 tons/ha (P3) and themaizeDampit localvariety (V1) showed good results on the growth and yield of maize crops. The results of P3V1 in maize plants were 2.66 kg of maize per bed and 1.15 kg of maize per bed. Keywords: Maize, Varieties, Vermicompost.